METAPHORICAL FORCES OF EXPRESSIONS IN LETTERS TO THE EDITORS IN BAHASA INDONESIA - Deli Nirmala (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
This study focuses on the metaphorical forces conveyed in the metaphorical expressions used in the letters to the editors, which are considered as the second- order meaning. Classified into existential, quantitative, qualitative, directional, spatial, motion, and temporal, these forces imply living experiences showing the existence, development, quality, movement, and space and time used by humans intheir lives in the world. The experiences built in the mind are activated when language is used.Keywords: metaphors, metaphorical forces, metaphorical expressions, second order of meaning